2020
DOI: 10.1111/1365-2435.13574
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus allocation to and resorption from leaves regulate the residence time of phosphorus in above‐ground forest biomass on Mount Kinabalu, Borneo

Abstract: The residence time of phosphorus (P) in trees is a consequence of plant adaptation to P deficiency, with longer P residence time on soils with low P availability. P residence time has been studied at the leaf or canopy level but seldom at the whole‐tree level. Whereas P residence time at the leaf or canopy level is largely determined by leaf longevity and the resorption of P before leaf abscission, P residence time at the whole‐tree level will also be influenced by differences in P allocation to different plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 56 publications
1
10
0
Order By: Relevance
“…The only and most remarkable difference was in wood P concentration, where we found a clear trend of all cerrado species allocating very high amounts of P to the sapwood and heartwood. Wood nutrient allocation directly affects nutrient residence time at the whole-tree level: nutrients allocated to the canopy lead to larger flux via fast turnover, meaning a shorter residence time, compared to nutrients allocated to wood biomass (Tsujii et al, 2020). Our results agree with the current literature suggesting that P in tropical ecosystems is a key limiting nutrient (Malhi et al, 2009;Quesada et al, 2010) and may affect transition ecosystem dynamics (Dionizio et al, 2018), suggesting two distinct strategies in the cerrado and cerradão vegetation.…”
Section: Discussionsupporting
confidence: 88%
“…The only and most remarkable difference was in wood P concentration, where we found a clear trend of all cerrado species allocating very high amounts of P to the sapwood and heartwood. Wood nutrient allocation directly affects nutrient residence time at the whole-tree level: nutrients allocated to the canopy lead to larger flux via fast turnover, meaning a shorter residence time, compared to nutrients allocated to wood biomass (Tsujii et al, 2020). Our results agree with the current literature suggesting that P in tropical ecosystems is a key limiting nutrient (Malhi et al, 2009;Quesada et al, 2010) and may affect transition ecosystem dynamics (Dionizio et al, 2018), suggesting two distinct strategies in the cerrado and cerradão vegetation.…”
Section: Discussionsupporting
confidence: 88%
“…C. mongolicum seedlings showed divergent responses to N enrichment and water addition. When plants allocate more nutrients to short‐lived organs, rather than to woody organs, it can lead to a larger loss of nutrients (Tsujii et al 2020). In our study, we found that more N and P were allocated to roots under drought stress, especially to fine roots (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Above‐ground net primary productivity was lower on ultrabasic than on sedimentary soils at the same elevation, and sharply decreased with increasing elevation on both soils (Kitayama & Aiba, 2002). Trees show more resource‐conservative traits on phosphorus‐deficient, low‐productivity forests across our study sites (Tsujii, Aiba, & Kitayama, 2020). Particularly, we were interested to know if/how resource‐conservation traits of trees influence vegetative periodicity.…”
Section: Introductionmentioning
confidence: 85%